THE EFFECT OF DIFFERENT NATURAL AND MANIFESTED CHANGES ON THE GROWTH AND SURVIVAL RATE OF FISH LARVA KOI (Cyprinus carpio) - Mardawi, Mardawi; Aryani, Netti; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted in July-June 2019 at the Fish Hatchery and Breeding Laboratory (PPI), Department of Aquaculture, Faculty of Fisheries and Marine, Riau University. This study aims to determine the effect of different natural feed substitutions on the growth and survival of koi fish larvae (Cyprinus carpio). The method used in this study was an experimental method. The design used was a one-factor Completely Randomized Design (CRD/RAL) with 6 (six) treatments and 3 (three) replications. The treatments applied in this study were: P1 = Feeding Artemia sp (0-10 days) + Shrimp Pellets (11-30 days), P2 = Feeding Artemia sp (0-10 days) + Tubifex sp (11-30 days), P3 = Feeding Artemia sp (0-10 days) + Tubifex sp (11-20 days) + Shrimp Pellets (21-30 days), P4 = Water Fleass feeding (0-10 days) + Shrimp Pellets (11-30 days), P5 = Water Fleass feeding (days 0-10 days) + Tubifex sp (11-30 days), P6 = WaterÂ  Fleass feeding (0-10 days) + Tubifex sp (11-20 days) + Shrimp Pellets (21-30 days). From the results of this study it can be concluded that the change in natural and artificial feed has a significant effect on the growth and survival of the koi fish larvae. The best treatment is obtained atP5 = Water fleas feed change (0 - 10 days) + Tubifex sp (11-30 days) with an average growth of 0.94 gram absolute weight, 4.32 cm absolute length growth, a specific growth rate of 16.64%/day, and 95.56% survival rate.The value of the water quality parameter is a temperature of 28-31oc,pH 5.4-6.5 and DO 4.1-5.2.Keywords: Replacement Growth, Fish Larvae Koi